(3efgGL GdWGdH Edi JMbjb GdcGajIs - (3CMeO Hf eMeO GdQUGUs; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG Cdgefi ef Yde GdYQHjI hHYO aEf GdebOeI GdMGLjI GdcGajI deG UGQJ efGWGJ ddYdhe GdCOHjI SCdfi ef jdRefi ESYGag Cf CJHY CdaGXgG HGdcTa hGdEjVGM s
(3BNQgG (B:s
(3BNQI ai GdcdGe Ydi fhf GdJhcjO (B: " (3hdG JHOd ZPG cGf bHdgG eVehekG , aGYQa Pdc ehabkG Ef TGA Gdgd Je cJGH efgGL GdWGdH s
(3GdfSNI HgG MhGTs
(3cJH eJf GdcGajI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdJhMjO hGdedd hGdfMds